2-(4-Chlorophenyl)-3-p-tolyl-1,3-thiazolidin-4-one - Sun, Xiao-Jun (International Union of Crystallography, 2009)
The title compound, C(16)H(14)ClNOS, a potent antibacterial chemical, features a dihedral angle of 49.4 (1)° between the 4-tolyl and thiazolidinone rings, and a dihedral angle of 87.2 (5)° between the thiazolidinone and 4-chlorophenyl rings.